EXPERT SYSTEM FOR CAT DISEASE DIAGNOSIS USING NAÏVE BAYES METHOD - Muhammad Brilian Kalam; Dian Asmarajati; Hidayatus Sibyan (Nacreva Publisher, 2023)
Many people choose cats as pets. Cats can benefit humans, but when cats are sick, they can suffer damage, just as cat disease does in humans. Lack of knowledge about the management of cats is one of the leading causes of the high incidence of diseases in cats. The wonosobo area, the cat keeper and the abundance of wild cats, is no exception to the knowledge and insight needed in caring for good cats, and even the number of experts and animal clinics in particular is small. Therefore it requires a system that supports the role of a veterinarian in treating cat diseases, where it can quickly and accurately diagnose diseases in cats based on symptoms of diseases in cats based on previous medical summarizations. Systems built on websites for accessibility and usage. The system's accuracy rate reached 90%, with a 95% f1 score to give the overall size of a model.